2020
DOI: 10.3390/biom10050679
|View full text |Cite
|
Sign up to set email alerts
|

A Biochemometric Approach for the Identification of In Vitro Anti-Inflammatory Constituents in Masterwort

Abstract: Peucedanum ostruthium (L.) Koch, commonly known as masterwort, has a longstanding history as herbal remedy in the Alpine region of Austria, where the roots and rhizomes are traditionally used to treat disorders of the gastrointestinal and respiratory tract. Based on a significant NF-κB inhibitory activity of a P. ostruthium extract (PO-E), this study aimed to decipher those constituents contributing to the observed activity using a recently developed biochemometric approach named ELINA (Eliciting Nature’s Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Similar biochemometrics approach has been extensively applied in natural products research as a preliminary evaluation step in the process of drug discovery from natural sources 31 34 . Hence, further integration with in silico approaches like neural network-based virtual screening that was applied in this investigation, can increase the success rate of targeting the bioactive metabolites in complex crude extracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar biochemometrics approach has been extensively applied in natural products research as a preliminary evaluation step in the process of drug discovery from natural sources 31 34 . Hence, further integration with in silico approaches like neural network-based virtual screening that was applied in this investigation, can increase the success rate of targeting the bioactive metabolites in complex crude extracts.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the previous extensive cheminformatic investigation, both physcion (1) and emodin (2) were validated this approach where they inhibited the in vitro plasmodial growth with IC 50 values of 0.9 and 1.9 µM, respectively. Similar biochemometrics approach has been extensively applied in natural products research as a preliminary evaluation step in the process of drug discovery from natural sources [31][32][33][34] . Hence, further integration with in silico approaches like neural network-based virtual screening that was applied in this investigation, can increase the success rate of targeting the bioactive metabolites in complex crude extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, we identified and isolated several bioactive compounds from PO by applying a novel biochemometric approach named Eliciting Nature’s Activities (ELINA; [ 18 , 130 ]) with an NF-ĸB reporter-gene assay plus two assays for E-selectin and VCAM-1 as biological read-out. However, the anti-inflammatory activity could only partially recovered (as compared to the total extract) by the combination of imperatorin and peucenin as a mixture, suggesting additional combinatorial effects [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some details on a few of the species: master-wort (belonging to the Apiaceae) has been cultivated in Fennoscandia and used to flavor beverages or for medicinal purposes [66]. Recent research has identified bioactive constituents as different furanocoumarins [67]. The plant is said to have been introduced to Fennoscandia in mediaeval time.…”
Section: Discussionmentioning
confidence: 99%